Organ Restoration With Normothermic Machine Perfusion and Immune Reaction - Parente, Alessandro; Osei-Bordom, Daniel-Clement; Ronca, Vincenzo; Perera, M. Thamara P. R.; Mirza, Darius (Frontiers in Immunology, 2020)
Liver transplantation is the only recognized effective treatment for end-stage liver disease. However, organ shortages have become the main challenge for patients and physicians within the transplant community, with waiting list mortality remaining around 10% worldwide. The post-transplantation period is also associated with adverse complication rates for specific cohorts of high-risk patients, particularly in relation to patient and graft survival. Ischaemia reperfusion injury (IRI) has been highlighted as the mechanism that increases parenchymal damage, eventually leading to significant graft dysfunction and other poor outcome indicators. In clinical practice, the consequences of IRI such as reperfusion syndrome, primary non-function of graft, allograft dysfunction, ischaemic biliary damage, and early biliary complications, can be life-threatening. This is because IRI dictates the development of a significant inflammatory immune response, which in turn drives the pathway to the eventuality of cell apoptosis. IRI’s primary mechanism is linked with significant mitochondrial damage due to low oxygen tension within the hepatic micro-environment and severe adenosine triphosphate (ATP) depletion during the ischaemic period. After the restoration of normal blood flow, this damage is further enhanced, as the mitochondria respond to reperfusion by releasing reactive oxygen species (ROS). ROS activates liver resident immune cells within the hepatic micro-environment, leading to a pro-inflammatory response and eventual parenchymal cell apoptosis and associated tissue degradation. Machine perfusion (MP) has been an emergent technique and is widely considered to be one of the most important research advances in organ preservation, restoration, and transplantation. Indeed, MP has the potential not only to rescue frequently discarded organs but also to limit the extent of IRI, leading to the suppression of the pro-inflammatory response. This suppressive immunomodulation has been proven to have a profound effect, reducing the prevalence of allograft rejection and the use of immunosuppression therapy, and minimising post-transplant complications. Despite the potential benefits, the mechanisms that reduce IRI and mediate the immune reactions within liver grafts during MP remain unclear. This review is aimed at updating current knowledge of MP, with a focus on normothermic machine liver perfusion (NMLP) and its potential role in immune response pathways.